2021
DOI: 10.1111/gcb.15979
|View full text |Cite
|
Sign up to set email alerts
|

Temperature impact on the influence of penguin‐derived nutrients and mosses on non‐native grass in a simulated polar ecosystem

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Nutrient limitation plays a major role in shaping polar communities (Zwolicki et al 2016;Bokhorst et al 2019Bokhorst et al , 2022Du et al 2020), but we only observed increasing response trends, with large variability among the 22 polar studies (Fig. 4).…”
Section: Climatic and Latitude Influencesmentioning
confidence: 72%
“…Nutrient limitation plays a major role in shaping polar communities (Zwolicki et al 2016;Bokhorst et al 2019Bokhorst et al , 2022Du et al 2020), but we only observed increasing response trends, with large variability among the 22 polar studies (Fig. 4).…”
Section: Climatic and Latitude Influencesmentioning
confidence: 72%
“…Although native terrestrial vertebrates are absent, breeding and molting populations of marine mammals and birds are a key source of marine‐derived nutrient supplies (Bokhorst et al, 2019). It is very likely that these marine animals will alter their movements with the changing climate (McCarthy et al, 2019), which can have significant implications for terrestrial nutrient availability (Bokhorst et al, 2022).…”
Section: The Environment Is Changingmentioning
confidence: 99%
“…Changes from mosses to lichens induced by environmental change are accompanied by changes in the communities that live within these vegetation types (e.g., diatom composition, see Bishop et al, 2021 ). On the Antarctic Peninsula, mosses often provide a nursery for establishment of vascular plants, which may then outcompete them (Bokhorst et al, 2022 ; Casanova‐Katny & Cavieres, 2012 ).…”
Section: Live Mosses and Peatsmentioning
confidence: 99%